2005
DOI: 10.4161/cc.4.5.1690
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitors of Histone Deacetylases Alter Kinetochore Assembly by Disrupting Pericentromeric Heterochromatin

Abstract: The kinetochore, a multi-protein complex assembled on centromeric chromatin in mitosis, is essential for sister chromosome segregation. We show here that inhibition of histone deacetylation blocks mitotic progression at prometaphase in two human tumor cell lines by interfering with kinetochore assembly. Decreased amounts of hBUB1, CENP-F and the motor protein CENP-E were present on kinetochores of treated cells. These kinetochores failed to nucleate and inefficiently captured microtubules, resulting in activat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
93
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(108 citation statements)
references
References 40 publications
12
93
0
2
Order By: Relevance
“…62 In contrast, normal primary human cells tolerated HDIs quite well, despite minor chromosome segregation defects and a delay to progression through mitosis, as described by others previously. [63][64][65][66][67] We also found that in normal primary human cells not expressing HP1bDN, treatment with HDIs caused a rapid relocalization of endogenous HP1 proteins to pericentromeric regions, adjacent to chromosome kinetochores. 62 This relocalization was blocked in the cells expressing HP1bDN.…”
Section: The Cellular Role Of Hp1 Proteinssupporting
confidence: 53%
“…62 In contrast, normal primary human cells tolerated HDIs quite well, despite minor chromosome segregation defects and a delay to progression through mitosis, as described by others previously. [63][64][65][66][67] We also found that in normal primary human cells not expressing HP1bDN, treatment with HDIs caused a rapid relocalization of endogenous HP1 proteins to pericentromeric regions, adjacent to chromosome kinetochores. 62 This relocalization was blocked in the cells expressing HP1bDN.…”
Section: The Cellular Role Of Hp1 Proteinssupporting
confidence: 53%
“…However, at similar submicromolar concentrations belinostat is unable to induce a strong mitotic arrest in the resistant DLBCL cell lines. Studies of the mitotic effects of HDACi in other cell types have established that, in addition to activating the SAC, they cause it to fail prematurely and induce apoptotic signaling 17,19,30,31 ). We therefore hypothesized that forced mitotic arrest in the resistant cells might sensitize them to belinostat-induced cytotoxicity.…”
Section: Resultsmentioning
confidence: 99%
“…17,19 HDAC inhibition causes destabilized interactions between microtubules (Mt) and kinetochores assembled at centromeres. 17,31 A recent study showed that aberrant acetylation of the Mt endbinding protein, EB1, prevents stable chromosome alignment at the metaphase plate. 47 SAC activation prevents progression or with belinostat (Bel) and vincristine (VCR) either alone or in combination for 48 h prior to harvest as shown below the timeline.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In culture with TSA, histones in newly synthesized chromatin remain acetylated, and this disrupts the structure and function of the centromere and the pericentric heterochromatin, with loss of binding to heterochromatin binding proteins (Taddei et al, 2001;Cimini et al, 2003). Histone acetylation interferes with histone phosphorylation and disrupts the function of mitotic spindle checkpoint proteins, such as BubR1, hBUB1, CENP-F and CENP-E (Dowling et al, 2005;Robbins et al, 2005). As a result, the cells show a transient arrest at prometaphase, followed with aberrant mitosis such as missegregation and loss of chromosomes, resulting in cell death by either apoptosis or, mitotic cell death/ catastrophe (Qiu et al, 2000;Cimini et al, 2003;Xu et al, 2005).…”
Section: Hdaci Induces Mitotic Cell Deathmentioning
confidence: 99%